How socially responsible human resource management fosters work engagement: The role of perceived organizational support and affective organizational commitment - Pimenta, S. (2023)
Purpose – In recent years, efforts to reinforce the links between corporate social responsibility and human resource management have highlighted employees’ role as crucial organizational stakeholders. This study aims to investigate whether workers’ perception of socially responsible human resource management (SR-HRM) based on employee-focused practices is related to work engagement (WE). This research also explored whether perceived organizational support (POS) and affective commitment (AC) can contribute to explaining this relationship. Social exchange theory and job demands-resources model were used to theoretically frame the research. Design/methodology/approach – Data were collected from a sample of 222 employees working in diverse organizations, using individual online surveys. Several analyses were conducted to assure data robustness to common method bias. Findings – The results confirm that SR-HRM fosters WE and that this effect is subject to sequential mediation by POS and AC. Accordingly, SR-HRM practices contribute to higher level of POS, which then foster stronger affective bonds with employers and, in turn, higher levels of vigor, absorption and dedication among workers. Originality/value – The findings contribute to the expansion of the SR-HRM literature by providing a deeper understanding of how this management strategy affects employees’ job-related attitudes, particularly WE a much-overlooked variable in this realm.